"These Are the Ones to Order--the Light Ones!" - Dow Chemical Company (1946)
Color print advertisement for the Dow Chemical Company's Magnesium Division. The advertisement depicts two men discussing the purchase of tools made from Dowmetal, a product marketed for its lightness and durability relative to other structural metals. This advertisement appeared on page 41 of the February 23, 1946 edition of The Saturday Evening Post.
Keywords: Magnesium; Dow Chemical Company; Corporations; Advertising; Magnesium industry and trade; Chemical industry